2007
DOI: 10.1007/s10549-007-9710-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of the upper limb following surgery and radiation for breast cancer

Abstract: The aim of this systematic review was to identify the prevalence and severity of upper limb problems following surgery and radiation for early breast cancer. Additionally, the independent prognostic contribution of radiation, type of breast surgery, type of axillary surgery, age and body mass index (BMI) was evaluated. Searches of electronic databases were conducted to identify articles that reported upper limb and quality of life outcomes after breast cancer surgery and external radiation. Eligible studies fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
170
1
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(189 citation statements)
references
References 58 publications
8
170
1
8
Order By: Relevance
“…2 Another systematic review indicated that the prevalence of shoulder and arm pain is between 9% and 68% and that pain persists in more than 20% of patients at 30 months after surgery. 8 The causes of shoulder pain related to breast cancer are thought to include muscle tightness, neurogenic pain due to lymph node removal, axillary cording, edema formation, and adhesive capsulitis resulting from restricted shoulder motion. 9 Recent research has indicated that physiotherapy interventions after breast cancer surgery are effective in improving shoulder ROM and function as well as reducing the occurrence of lymphedema and improving quality of life.…”
mentioning
confidence: 99%
“…2 Another systematic review indicated that the prevalence of shoulder and arm pain is between 9% and 68% and that pain persists in more than 20% of patients at 30 months after surgery. 8 The causes of shoulder pain related to breast cancer are thought to include muscle tightness, neurogenic pain due to lymph node removal, axillary cording, edema formation, and adhesive capsulitis resulting from restricted shoulder motion. 9 Recent research has indicated that physiotherapy interventions after breast cancer surgery are effective in improving shoulder ROM and function as well as reducing the occurrence of lymphedema and improving quality of life.…”
mentioning
confidence: 99%
“…Giderek artan meme kanserli kadın sayısı ile birlikte tedavi yan etkilerinin morbiditesini saptamak ve azaltmak yüksek önceliğe sahip olup son yıllarda araştırmaların odağı haline gelmiştir (21).…”
Section: Discussionunclassified
“…Physiotherapeutic treatment concomitant to radiotherapy is very important, because it minimizes the side effects, such as subcutaneous fibrosis, limitations on shoulder range of motion, muscle weakness and pains (Lee et al, 2008). In outpatient rehabilitation, in addition to individualized attendance, it is also undertaken in collective groups.…”
Section: Postoperative Follow-upmentioning
confidence: 99%